Association of physical activity on the functional connectivity of the hippocampal–orbitofrontal pathway. Issue 3 (3rd July 2019) - Ikuta, Toshikazu; Frith, Emily; Ponce, Pamela; Loprinzi, Paul D.
ABSTRACT: Objective : The objective of the study is to examine the association between physical activity and hippocampal–orbitofrontal functional connectivity. Methods : Data from the Nathan Kline Institute-Rockland Sample was utilized, which consisted of 366 participants ( M age  = 43 years; 63% female). Physical activity was self-reported using the International Physical Activity Questionnaire. Hippocampal–orbitofrontal functional connectivity was assessed from magnetic resonance imaging. Results : Moderate-intensity physical activity was not statistically significantly associated with left hippocampal–orbitofrontal connectivity ( β  = 0.001; 95% CI: −0.02, 0.03; P = 0.90) or right hippocampal–orbitofrontal connectivity ( β  = 0.01; 95% CI: −0.01, 0.04; P = 0.22). However, vigorous-intensity physical activity was statistically significantly associated with right hippocampal–orbitofrontal connectivity ( β  = 0.01; 95% CI: 0.004, 0.02; P = 0.002). Discussion : Habitual engagement in intense physical activity was associated with greater hippocampal–orbitofrontal connectivity, while moderate activity engagement was not. This may have important implications for the exercise neurobiology field in the context of exercise and memory function, suggesting that intense activity may facilitate cognitive/memory functions. However, our findings should be interpreted with caution given the relatively weak associations that were observed.